Epigenetics and Colorectal Neoplasia: the Evidence for Physical Activity and Sedentary Behavior - Hibler, Elizabeth (Curr Colorectal Cancer Rep, 2015)
Studies demonstrate that regular physical activity and, more recently, limited sedentary behavior are associated with reduced risk of colorectal neoplasia. However, the biological mechanisms of action for physical activity versus sedentary behavior are not clear. Epigenetic variation is suggested as a potential mechanism that would allow for independent, or possibly even synergistic, effects of activity and inactivity on colorectal epithelium. We describe the evidence for epigenetic variation as a link between physical activity and sedentary behavior in colorectal neoplasia risk. There are few studies that directly evaluate this relationship. However, the growing literature describes a variety of gene targets influenced by activity that are also important to colorectal neoplasia etiology. Future studies may identify epigenetic markers with translational significance in identifying high-risk individuals or those for whom a personalized activity regimen could significantly alter the methylation signature in colon epithelial cells, and thus future risk of colorectal cancer.